Pengaruh Heptagon Fraud Terhadap Fraudulent Financial Statement Pada Perusahaan Basic Materials Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2024 - Raulina Br. Sitinjak; Duma Megaria Elisabeth; Ivo Maelina Silitonga (Politeknik Raflesia Press, 2026)
Statements. The population of this study is companies in the Basic Materials sector listed on the Indonesia Stock Exchange for the 2021-2024 period. The study population was 109 companies with 41 of them being a sample that met the criteria. The technique used is purposive sampling. The data analysis technique used was multiple linear regression processed using SPSS 25. The results of this study show that Pressure, Rationalization has no effect on Fraudulent Financial Statements. Opportunity, Capability, Arrogance have a positive or insignificant effect on Fraudulent Financial Statements. Meanwhile, Culture has a negative and significant effect on Fraudulent Financial Statements and Religiosity has a positive and significant effect on Fraudulent Financial Statements. And simultaneous testing proves that Pressure, Opportunity, Rationalization, Capability, Arrogance, Culture, and Religiosity have a significant effect on Fraudulent Financial Statements. In the Coefficient of Determination Test, the results obtained that the variables Pressure, Opportunity, Rationalization, Capability, Arrogance, Culture, and Religiosity were able to explain 8.9% of the variation in Fraudulent Financial Statements. Meanwhile, the remaining 91.1% were influenced by other variables outside the research model.